2017
DOI: 10.1609/aaai.v31i1.10933
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Curriculum Graph Generation for Reinforcement Learning Agents

Abstract: In recent years, research has shown that transfer learning methods can be leveraged to construct curricula that sequence a series of simpler tasks such that performance on a final target task is improved. A major limitation of existing approaches is that such curricula are handcrafted by humans that are typically domain experts. To address this limitation, we introduce a method to generate a curriculum based on task descriptors and a novel metric of transfer potential. Our method automatically generates a cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…But current DRL-based dialogue policy approaches mostly remain brute-force random sampling training, improving their performance at the expense of high interaction costs (Jiang et al, 2015;Ren et al, 2018;Narvekar and Stone, 2019;Narvekar et al, 2020). Inspired by human education, a novel training paradigm, curriculum learning (CL), is proposed to improve learning performance and efficiency through training a model on a designed sequence of training tasks, rather than an arbitrary random sampling (Svetlik et al, 2017;Fan et al, 2018;Racanière et al, 2019;Green et al, 2019). Although many empirical studies demonstrated beneficial effects of CL, reporting in the field of dialogue policy remains very limited (Zhao et al, 2021a;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…But current DRL-based dialogue policy approaches mostly remain brute-force random sampling training, improving their performance at the expense of high interaction costs (Jiang et al, 2015;Ren et al, 2018;Narvekar and Stone, 2019;Narvekar et al, 2020). Inspired by human education, a novel training paradigm, curriculum learning (CL), is proposed to improve learning performance and efficiency through training a model on a designed sequence of training tasks, rather than an arbitrary random sampling (Svetlik et al, 2017;Fan et al, 2018;Racanière et al, 2019;Green et al, 2019). Although many empirical studies demonstrated beneficial effects of CL, reporting in the field of dialogue policy remains very limited (Zhao et al, 2021a;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We may also consider more automatic sequencing strategies, such as using a subtask set to calculate transfer potential (Svetlik et al, 2017;Silva and Costa, 2018). However, we leave it as future work and focus on how to transfer the knowledge learned from intermediate tasks to improve performance in the target task.…”
Section: Task Sequencingmentioning
confidence: 99%
“…Depending on the problem itself, various domain-specific measures could also be used for difficulty evaluation [12], further complicating the issue. Furthermore, all existing research efforts on generating tasks for CL in RL have focused on attempting to automate the process and all involve some degree of limitation [22].…”
Section: Curriculum Learningmentioning
confidence: 99%